INFLUENCE EDUCATIONAL COMPETENCE LENGTH SERVICE ON SHIP CREW PERFORMANCE THROUGH WORK ENGAGEMENT - Hendra Gunawan Sitepu; Robert Tua Siregar; Fajar Rezeki Ananda Lubis (Nurul Jadid University, 2026)
This study aims to analyze the effects of competence, education, and length of service on the performance of shipboard employees, as well as the mediating role of work engagement at PT Temas Shipping. The study involved all shipboard employees, with a total population of 50 people. Data were collected using primary data in the form of a 1–5 Likert-scale questionnaire that had been tested for validity and reliability. Data analysis employed a quantitative survey method. The findings indicate that: competence has a positive and significant effect on work engagement, ( education has a positive and significant effect on work engagement, length of service has a positive and significant effect on work engagement, competence has a positive and significant effect on performance, education has a positive and significant effect on performance, length of service has a positive and significant effect on performance, work engagement has a positive and significant effect on performance, competence affects performance through work engagement as an intervening variable, education affects performance through work engagement as an intervening variable and length of service affects performance through work engagement as an intervening variable.